Nevanlinna–Pick Problem for Stieltjes Matrix Functions - Dyukarev, Yu. M. (Ukrains’kyi Matematychnyi Zhurnal, 2004)
We consider the Nevanlinna–Pick interpolation problem for Stieltjes matrix functions. We obtain two criteria for the indeterminacy of the Nevanlinna–Pick problem with infinitely many interpolation nodes. In the indeterminate case, we describe the general solution of the Nevanlinna–Pick problem in terms of fractional-linear transformations.